The impact of cognitive stimulation in older adults with dementia - Teixeira,Carla M. (2024)
Abstract This study evaluated the impact of a cognitive stimulation program on older adults diagnosed with dementia. The sample comprised 22 participants aged 73-95, randomly assigned to an experimental group (N = 12) and a control group (N = 10). While no statistically significant decreases were observed in the studied dimensions, clinically relevant gains were noted: 41.70% in cognition, 41.60% in quality of life, and 8.3% in functional skills. Although no therapeutic interventions have successfully reversed dementia, healthcare providers reported improvements in participants’ social interactions, behaviors, and engagement in daily institutional routines. These observations suggest tangible benefits from program participation. It’s important to note that staff working closely with these patients daily observed these improvements despite the lack of statistically significant results. This discrepancy highlights the potential limitations of relying solely on quantitative measures to assess such interventions’ effectiveness. In conclusion, the cognitive stimulation program shows promise as a potential tool for slowing dementia-associated degenerative processes, particularly in areas that standard quantitative assessments may not fully capture. Further research with larger sample sizes and more sensitive measures may be warranted to fully understand the program’s impact.